Promoting Responsible Business Practices: A Case of Chambers of Commerce - Braendle, Udo; Rahdari, Amir Hossein; Dehkordi, Hassan Farajzadeh (Revista Internacional de Organizaciones, 2016)
Employer organizations and business associations are the advocates of private organizations' interests. They also provide a platform for private enterprises to tap into synergetic and collaborative opportunities. Chambers of commerce, in particular, as well-organized establishments in the business environment are in a unique position to guide and assist organizations to thrive and stay competitive. To this end, recently, chambers of commerce have embarked on fostering responsible business practices among their members. The raison d'être behind this movement and the types of action taken have been largely neglected by the academic research. This study examines a number of leading chambers of commerce and business associations from both developed and developing countries in an attempt to shed light on the current responsible business practices in these organizations.